PENGARUH TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, TEKANAN ANGGARAN WAKTU DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGMENT (Studi Empiris pada Kantor Akuntan Publik di Kota Pekanbaru, Medan dan Batam) - Hernisa Soleha; Ruhul Fitrios; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2026)
This study examines the effects of obedience pressure, task complexity, time budget pressure, and auditor experience on audit judgment among auditors working at Public Accounting Firms (KAP) in Pekanbaru, Medan, and Batam. A quantitative survey approach was employed using saturated sampling. Data were collected from 88 auditors through a five-point Likert scale questionnaire and analyzed using multiple linear regression. The results reveal that obedience pressure and auditor experience have a positive and significant effect on audit judgment, while task complexity and time budget pressure have a negative and significant effect. These findings indicate that greater pressure from superiors or clients influences auditors’ judgments, whereas increased task complexity and time constraints reduce judgment quality. Conversely, experienced auditors tend to produce more accurate and higher-quality audit judgments. The study highlights the importance of managing work pressure, controlling task complexity, allocating adequate audit time, and enhancing auditor experience to improve audit judgment quality in Public Accounting Firms. Keywords: Audit Judgment, Obedience Pressure, Task Complexity, Time Budget Pressure, Auditor Experience, Public Accounting Firm